   Symbol

# Calculator search results

Formula
Solve the equation
Answer Graph
$y = 2 x - 4$
$y = 2 \left ( x - 1 \right ) + 3$
$x$Intercept
$\left ( 2 , 0 \right )$
$y$Intercept
$\left ( 0 , - 4 \right )$
$x$Intercept
$\left ( - \dfrac { 1 } { 2 } , 0 \right )$
$y$Intercept
$\left ( 0 , 1 \right )$
$2x-4 = 2 \left( x-1 \right) +3$
 Do not have the solution 
Solve the equation
$2 x - 4 = \color{#FF6800}{ 2 } \left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) + 3$
 Multiply each term in parentheses by $2$
$2 x - 4 = \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } + 3$
$2 x - 4 = 2 x \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ + } \color{#FF6800}{ 3 }$
 Add $- 2$ and $3$
$2 x - 4 = 2 x + \color{#FF6800}{ 1 }$
$2 x - 4 = \color{#FF6800}{ 2 } \color{#FF6800}{ x } + 1$
 Move the variable to the left-hand side and change the symbol 
$- 4 = 1$
$\color{#FF6800}{ - } \color{#FF6800}{ 4 } = \color{#FF6800}{ 1 }$
 This equation is false because all of the values calculated by all terms are different 
 Do not have the solution 
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture